Why Do We Respond to a Concession with Another Concession? Reciprocity and Compromise. Issue 1 (January 2017) - Thuderoz, Christian
Abstract : All negotiation processes involve an exchange of concessions, and compromise is an agreement based on mutual concessions. Hence the questions investigated in this article: Why are concessions in negotiations always reciprocal? Why do negotiators follow this rule? And why do negotiators achieve these concessions through a process that we call compromise? Is there a connection between conceding and promising? In this article, I examine the structure of concession making and compromise through sociological, anthropological, and etymological lenses to better illuminate this critical negotiation component.